Effectiveness of forward and retro walking in subjects with osteoarthritis of knee: A comparative study - Anantha Jyothi, Pothula S.V.V.; Apparao, Patchava; Swamy, Ganapathi; Chaturvedhi, P.; Mounika, R. Geetha (Journal of Dr. NTR University of Health Sciences, 2024)
ABSTRACT Background and Objective: Osteoarthritis is a degenerative joint disease that leads to biomechanical and morphological alterations in the joint. There are various physiotherapeutic interventions available for treating osteoarthritis but there is lack of literature regarding comparison of effectiveness of Forward walking and Retro walking in subjects with Osteoarthritis of knee, hence the need of the study arises. The purpose of this study was to determine the effectiveness between the Forward Walking and Retro-Walking in improving Strength and Function in subjects with Osteoarthritis of Knee. Methods: Prospective Cohort study design. 150 subjects who were clinically diagnosed of Osteoarthritis of Knee were assessed and only 66 were recruited who are willing to be in the study and they were randomly allocated into two Groups. In Group I (n = 33) subjects were treated with Conventional Physiotherapy and Forward Walking for 8 weeks, whereas in Group II (n = 33) subjects were treated with Conventional Physiotherapy and Retro Walking for 8 weeks. The outcome of this intervention Function (KOOS) and lower limb strength (knee flexion and extension). Results: Statistical analysis of this study data revealed that in between-group comparison showed there is a STATISTICAL significant difference in KOOS and knee flexors and extensors strength. Conclusion: This study concluded that Retro Walking is a suitable adjunct to Conventional Physiotherapy in Subject with knee osteoarthritis.